Pengaruh Gaya Kepemimpinan Transformasional terhadap Kinerja Karyawan Farina Beauty Clinic Karawang - Nandari Nur Iqnatia; Widya Kumala Dewi; Farida Asya; Linda Purnamasari; Umi Zahro Dewi Utami; Saniyyah Nurul Fadilah; Alma Arizulhaq (Journal of Economics, Management, and Accounting, 2026)
This study aims to analyze the effect of transformational leadership style on employee performance at Farina Beauty Clinic Karawang. The research employed a quantitative explanatory design using simple linear regression analysis. The population consisted of 33 active employees, all of whom were selected as the sample through a saturated sampling technique. Data were collected using a Likert-scale questionnaire and analyzed with IBM SPSS. The findings indicate that all research instruments were valid and reliable. The regression analysis produced the equation Ŷ = 7.130 + 0.515X with a coefficient of determination (R²) of 0.635, indicating that transformational leadership explains 63.5% of the variance in employee performance. The t-value of 7.351 with a significance level of 0.000 (<0.05) confirms a positive and significant effect of transformational leadership on employee performance. The novelty of this study lies in directly examining the relationship between the two variables in a beauty clinic setting without incorporating mediating variables, thereby providing new empirical evidence for human resource management in the beauty service industry